Metal Oxides: Zebrafish High‐Throughput Screening to Study the Impact of Dissolvable Metal Oxide Nanoparticles on the Hatching Enzyme, ZHE1 (Small 9–10/2013). Issue 9 (16th May 2013) - Lin, Sijie; Zhao, Yan; Ji, Zhaoxia; Ear, Jason; Chang, Chong Hyun; Zhang, Haiyuan; Low‐Kam, Cecile; Yamada, Kristin; Meng, Huan; Wang, Xiang; Liu, Rong; Pokhrel, Suman; et al.
<x xml:space="preserve">Abstract</x> Zebrafish is emerging as a model organism for the safety assessment and hazard ranking of engineered nanomaterials. On page 1776, A. E. Nel and co‐workers showcase a highly automated high‐throughput screening (HTS) platform using zebrafish embryos for the hazard assessment of 24 representative metal oxide nanoparticles. Through HTS analysis, four metal oxide nanoparticles are found to interfere with zebrafish embryo hatching. It is further demonstrated that hatching interference is a result of toxic metal ion shed from nanoparticles, compromising the zebrafish hatching enzyme 1 (ZHE1) activity. The structural and functional similarities of hatching enzymes across fish species suggest that the ZHE1 mechanistic paradigm could be used to predict the toxicity of a large number of engineered nanoparticles that may be hazardous to aquatic species. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>